The local co-evolution of firms and governments in the Information Age - Sarianna Lundan; John Cantwell (Journal of International Business Studies, 2020)
The governance structures of the value-creating activities of MNEs have evolved towards more networked forms that are geographically highly concentrated and involve partnering with diverse actors. The experimentation that takes place within these corporate networks has a parallel on the government side, where subnational governments, and particularly cities as hubs of economic activity, have increased their profile and level of cooperative activity. We argue that engagement in these partnerships is an essential way in which firms and governments co-evolve and create the basis for sustainable economic growth in the Information Age. While the origins of this collaborative form of governance reside in the increasing knowledge intensity of value creation, its implications go far beyond MNE value creation and capture, extending to issues of global governance such as climate change and sustainable development goals. We examine the implications of this process of co-evolution both in terms of the costs of developing the requisite corporate capabilities as well as the legitimacy of these efforts as part of a deliberative democracy.
Keywords: 330; theory of FDI and the MNE; knowledge transfer and innovation; economic geography; business–government interaction; multi-party cooperation